(untitled) (Journal of the College of Basic Education, 2026)
The study aimed to identify the impact of High-Intensity Interval Training (HIIT) on developing specific endurance and transitional speed among elite Iraqi football referees. Using an experimental approach with a one-group pre-test/post-test design, 12 referees from the Iraq Stars League were selected. The program lasted 8 weeks with 3 sessions per week. Results showed statistically significant differences in favor of the post-test for all physical variables. The study recommends integrating HIIT into the annual training plans for football referees.